2005
DOI: 10.1016/j.febslet.2005.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin recognition: In fish or not in fish?

Abstract: The interaction between pathogens and their multicellular hosts is initiated by activation of pathogen recognition receptors (PRRs). These receptors, that include most notably members of the toll-like receptor (TLR) family, recognize specific pathogen-associated molecular patterns (PAMPs). TLR4 is a central part of the receptor complex that is involved in the activation of the immune system by lipopolysaccharide (LPS) through the specific recognition of its endotoxic moiety (Lipid A). This is a critical event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
161
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(186 citation statements)
references
References 102 publications
(117 reference statements)
17
161
0
5
Order By: Relevance
“…It has been shown that in vitro cultured trout HK-derived adherent monocytes differentiate spontaneously and following incubation for several days develop a more mature, macrophage-like phenotype. This is manifested by changes in their morphology and enhanced potential to respond to LPS stimulation [17,28,29]. In the current study, the non-stimulated salmon primary cells displayed similar morphological changes when cultured in vitro for a period of 3 to 5 days (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…It has been shown that in vitro cultured trout HK-derived adherent monocytes differentiate spontaneously and following incubation for several days develop a more mature, macrophage-like phenotype. This is manifested by changes in their morphology and enhanced potential to respond to LPS stimulation [17,28,29]. In the current study, the non-stimulated salmon primary cells displayed similar morphological changes when cultured in vitro for a period of 3 to 5 days (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Fish have no or a poor inflammatory immune response to LPS (Berczi et al, 1966;Iliev et al, 2005;Swain et al, 2008). However, there are, to our knowledge, no studies about fish intestinal gut inflammation related to Edwardsiella LPS.…”
Section: Discussionmentioning
confidence: 93%
“…6h, i). Several reports suggest that fish do not respond to LPS mainly because of the lack of PLB, CD14 and TIRF1, essential components for the function of Toll-like receptor 4 (Iliev et al, 2005). Adult fish or zebrafish i.c.…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of TI-CAM2 have not been identified in teleosts [15,16,40], Xenopus, [22] or chickens [17,23], except in mammals and sharks [21]. As two TICAM homologs were identified in lamprey [14], Iliev et al [40] assumed that a TI-CAM2 ortholog existed in the common predecessor of fish and tetrapods. Sullivan et al confirmed this hypothesis and went further by suggesting that TICAM2 was probably lost after the divergence of rayfin and lobefin fishes 450 million years ago [17].…”
Section: Discussion Bbtticam Is the Earliest Ortholog Of Vertebrate Tmentioning
confidence: 99%
“…In the early vertebrates, TICAM1 is evolutionarily conserved and easily identified [40]. Homologs of TI-CAM2 have not been identified in teleosts [15,16,40], Xenopus, [22] or chickens [17,23], except in mammals and sharks [21].…”
Section: Discussion Bbtticam Is the Earliest Ortholog Of Vertebrate Tmentioning
confidence: 99%